Skillful hiding: evaluating hedge fund managers' performance based on what they hide. Issue 7 (7th February 2017) - Malladi, Rama; Fabozzi, Frank J.
ABSTRACT: Mandatory disclosure of hedge fund portfolios has been a hotly debated topic. This article studies asset returns of 'confidential holdings' (confidentiality treatment [CT]) or those assets that were not voluntarily disclosed by US-based hedge funds in their original 13F filings to the Securities and Exchange Commission. After analysing returns from 1999 to 2013, we find that in aggregate, the CT position size, ownership share and returns are statistically different to non-CT positions. We provide a mechanism for regulators and investors to rank fund managers based on what they hide in positions.